Ameliorative Potential of Hot Compress on Sciatic Nerve Pain in Chronic Constriction Injury-Induced Rat Model - Chan, Kwan-Yu; Tsai, Wen-Ching; Chiang, Chien-Yi; Sheu, Meei-Ling; Huang, Chih-Yang; Tsai, Yi-Ching; Tsai, Chia-Yun; Lu, Chia-Jung; Ho, Zih-Ping; Lai, De-Wei (Frontiers in Synaptic Neuroscience, 2022)
Hot compress modalities are used to ameliorate pain despite prevalent confusion about which modality should be used and when. Most recommendations for hot compresses are based on empirical experience, with limited evidence to support its efficacy. To obtain insight into the nerve transmission mechanism of hot compresses and to identify the nerve injury marker proteins specifically associated with sciatic nerve pain, we established a rat model of chronic constriction injury (CCI) and performed mechanical allodynia, electrophysiology, and histopathological analysis. All CCI rats exhibited geometric representation of the affected hind paw, which indicated a hyper-impact on both mechanical gait and asymmetry of gait on day 28. The CCI model after 28 days of surgery significantly reduced compound muscle action potential (CMAP) amplitude, but also significantly reduced latency. Administration of hot compress for 3 weeks (heated at 40–42℃, cycle of 40 min, and rest for 20 min, three cycles each time, three times per week) significantly increased the paw withdrawal thresholds in response to stimulation by Von Frey fibers and reversed the CCI-induced reduced sciatic functional index (SFI) scores. Hot compress treatment in the CCI model improved CMAP amplitude and latency. The S100 protein expression level in the CCI+hot compress group was 1.5-fold higher than in the CCI group; it dramatically reduced inflammation, such as Tumor necrosis factor alpha and CD68 expression in nerve injury sites. Synaptophysin (Syn) expression in the CCI+hot compress group was less than 3-fold in the CCI group at both nerve injury sites and brain (somatosensory cortex and hippocampus). This finding indicates that local nerve damage and inflammation cause significant alterations in the sensorimotor strip, and hot compress treatment could significantly ameliorate sciatic nerve pain by attenuating Syn and inflammatory factors from local pathological nerves to the brain. This study determines the potential efficacy and safety of hot compress, and may have important implications for its widespread use in sciatic nerve pain treatment.